Implementasi Program Pengembangan Perikanan Tangkap Pada Dinas Pertanian Dan Perikanan Kota Pekanbaru - Eko Handrian; Siti Hawa (JIAP (Jurnal Ilmu Administrasi Publik), 2022)
This study aims to determine and implement the Capture Fisheries Development Program at the Pekanbaru City Agriculture and Fisheries Service, the assessment indicators used include Policy Standards and Targets, Resources, Inter-Organizational Relations, Characteristics of Implementing Agencies, Social, Political and Economic Conditions. This type of research uses descriptive quantitative research methods with data collection techniques used consisting of primary data collected by questionnaires and interviews, and secondary data collected using observation and documentation. Based on the results of the research, it is known that in this study from the side of the official apparatus that the implementation of the Capture Fisheries Development program at the Pekanbaru City Agriculture and Fisheries Service is "implemented". This is because it is seen from an internal point of view, namely the official apparatus that the Pekanbaru City Agriculture and Fisheries Service as the executor of the Capture Fisheries Development program at the Pekanbaru City Agriculture and Fisheries Service has been carried out properly and seen from the community's point of view as an external party that, to realize the Development program Capture Fisheries at the Pekanbaru City Agriculture and Fisheries Service, it is very important to carry out outreach to the community, this is also to help the community become more aware that the government has provided a Capture Fisheries Development program at the Pekanbaru City Agriculture and Fisheries Service and the public is also not lacking in public information. . However, the activities and programs carried out are not in accordance with the philosophy of the capture fisheries development program at the Pekanbaru City Agriculture and Fisheries Office